PERANAN BAURAN PEMASARAN DALAM UPAYA MENINGKATKAN KEPUASAN DAN LOYALITAS KONSUMEN HOTEL - Cuk Taruna Hendrajaya (Jurnal Manajemen dan Bisnis, 2014)
The purpose of this study 1) To determine the effect of price on consumer satisfactionfactor The Kunja Bali? 2) To determine the influence of product to consumer satisfaction TheKunja Bali? 3) To determine the effect of promotions on consumer satisfaction factor TheKunja Bali? 4) To determine the effect of service quality on customer satisfaction The KunjaBali? 5) To determine the effect of site factors on consumer satisfaction The Kunja Bali? 6) Todetermine the effect of customer satisfaction on consumer loyalty Hotel The Kunja Bali?The study found 1) From the structural equation showed Regression Weight ) seen thereare three variables are significant positive effect,?( namely the effect of price (X2) of theConsumer Satisfaction (Y), the effect of Quality of Service (X5) of the Consumer Satisfaction(Y), the influence Consumer satisfaction (Y) to the Consumer Loyalty (Z) There is no significantpositive effect between the product (X1) of the Consumer Satisfaction (Y), the influence of place(X3) of the Consumer Satisfaction (Y) and the effect of promotion (X4) of the ConsumerSatisfaction ( Y) 2) Effect on Product (X1), price (X2), place (X3), Promotion (X4), Quality ofService (X5) of the Consumer Satisfaction (Y) is equal to 90.8%, and the influence of consumersatisfaction (Y ) of the Consumer Loyalty (Z) of 60.3%.Keywords: marketing mix, customer satisfaction and customer loyalty